"Wearing-off" efficacy of CGRP monoclonal antibodies for migraine prevention: A meta-analysis of randomized controlled trials. (April 2023) - Asawavichienjinda, Thanin; Sathitratanacheewin, Seelwan; Chokesuwattanaskul, Ronpichai
Background: A new migraine prevention, CGRP monoclonal antibodies (mAbs), is injectable on a monthly or quarterly basis. In clinical practice, some patients reported that drug effectiveness does not last until the upcoming scheduled injection, a so-called "wearing-off" effect. We aimed to evaluate the wearing-off effect of the CGRP mAbs for migraine prevention in patients with different monthly migraine days. Methods: We conducted a literature search for studies that reported migraine frequency after CGRP monoclonal antibody administration from MEDLINE, SCOPUS, Web of Science, and Cochrane Database from inception through February 2022. A meta-analysis, random-effects model was applied to assess the difference in migraine frequency between early and later weeks after medication to assess the presence of a wearing-off effect. Risk ratio was calculated to report the pooled treatment effect. Results: Four studies were entered for the analysis, comprising 2409 patients in randomized controlled trials. There was no association between CGRP mAbs and wearing-off effect in patients with galcanezumab with a pooled risk ratio of 1.29 (95% CI 0.73 to 2.28) compared to placebo group. However, there was an association between galcanezumab and wearing-off effect in patients with chronic migraine with a pooled risk ratio of 1.91 (95% CI 1.11 to 3.28) compared to placebo group. Conclusion: In this meta-analysis, there was a wearing-off efficacy of galcanezumab but only in a small percentage of patients with chronic migraine in randomized controlled trials.